Laboratório de IPv6 : aprenda na prática usando um emulador de redes - Moreiras, Antonio Marcos; Santos, Rodrigo Regis dos; Harano, Alexandre Yukio; Cordeiro, Edwin Santos; Nakamura, Tiago Jun; Morales, Eduardo Barasal; Ganzeli, Heitor de Souza; Carnier, Rodrigo Matos; Lugoboni, Gustavo Borges (Novatec, 2015)
417